Manual development and pilot randomised controlled trial of mindfulness-based cognitive therapy versus usual care for parents with a history of depression - Kuyken, W (Springer US, 2016)
Parental depression can adversely affect parenting and children's development. We adapted mindfulness-based cognitive therapy (MBCT) for parents (MBCT-P) with a history of depression and describe its development, feasibility, acceptability and preliminary estimates of efficacy. Manual development involved interviews with 12 parents who participated in MBCT groups or pilot MBCT-P groups. We subsequently randomised 38 parents of children aged between 2 and 6 years to MBCT-P plus usual care (n=19) or usual care (n=19). Parents were interviewed to assess the acceptability of MBCT-P. Preliminary estimates of efficacy in relation to parental depression and children’s behaviour were calculated at 4 and 9 months post-randomisation. Levels of parental stress, mindfulness and self-compassion were measured. Interviews confirmed the acceptability of MBCT-P; 78% attended at least half the sessions. In the pilot RCT, at 9 months, depressive symptoms in the MBCT-P arm were lower than in the usual care arm (adjusted mean difference = -7.0; 95% CI: -12.8 to -1.1; p=0.02) and eleven participants (58%) in the MBCT-P arm remained well compared to six (32%) in the usual care arm (mean difference = 26%; 95% CI: -4% to 57%; p = 0.02). Levels of mindfulness (p=0.01) and self-compassion (p = <0.001) were higher in the MBCT-P arm, with no significant differences in parental stress (p=0.2) or children’s behaviour (p=0.2). Children’s behaviour problems were significantly lower in the MBCT-P arm at 4 months (p=0.03). This study suggests MBCT-P is acceptable and feasible. A definitive trial is needed to test its efficacy and cost effectiveness.